Acute cyclooxygenase inhibition does not alter muscle sympathetic nerve activity or forearm vasodilator responsiveness in lean and obese adults. Issue 7 (17th July 2014) - Barnes, Jill N.; Charkoudian, Nisha; Matzek, Luke J.; Johnson, Christopher P.; Joyner, Michael J.; Curry, Timothy B.
Abstract Obesity is often characterized by chronic inflammation that may contribute to increased cardiovascular risk via sympathoexcitation and decreased vasodilator responsiveness. We hypothesized that obese individuals would have greater indices of inflammation compared with lean controls, and that cyclooxygenase inhibition using ibuprofen would reduce muscle sympathetic nerve activity (MSNA) and increase forearm blood flow in these subjects. We measured MSNA, inflammatory biomarkers (C‐reactive protein [CRP] and Interleukin‐6 [IL‐6]), and forearm vasodilator responses to brachial artery acetylcholine and sodium nitroprusside in 13 men and women (7 lean; 6 obese) on two separate study days: control (CON) and after 800 mg ibuprofen (IBU). CRP (1.7 ± 0.4 vs. 0.6 ± 0.3 mg/L; P < 0.05) and IL‐6 (4.1 ± 1.5 vs. 1.0 ± 0.1pg/mL; P < 0.05) were higher in the obese group during CON and tended to decrease with IBU (IL‐6: P < 0.05; CRP: P = 0.14). MSNA was not different between groups during CON (26 ± 4 bursts/100 heart beats (lean) versus 26 ± 4 bursts/100 heart beats (obese); P = 0.50) or IBU (25 ± 4 bursts/100 heart beats (lean) versus 30 ± 5 bursts/100 heart beats (obese); P = 0.25), and was not altered by IBU. Forearm vasodilator responses were unaffected by IBU in both groups. In summary, an acute dose of ibuprofen did not alter sympathetic nerve activity or forearm blood flow responses in healthy obese individuals, suggesting that the cyclooxygenase pathway is not a major contributor to these variables in this group.